Renal hemodynamics disturbances in early stages of arterial hypertension in young patients - I. G. Fomina; E. N. Gavrilova; T. A. Dyakova; N. E. Gaidamakina (Кардиоваскулярная терапия и профилактика, 2005)
Arterial hypertension (AH) is the most prevalent disease worldwide, with general population prevalence of 15-20%. Despite being typically diagnosed after the age of 50, recently AH becomes more prevalent in adolescents and young adults. Aim. To identify the first clinical signs of renal pathology in young patients (under 35) with initial stages of AH. Material and methods. Forty-two men with Stage I-III AH, aged 15-35 (mean age 21.7±5.6 years), were examined. AH duration varied from 1 to 7 years (3.6±3.0). Mean systolic blood pressure (BP) level was 149.35±9.03 mm Hg, diastolic BP – 93.48±5.32 mm Hg. In all participants, general clinical examination, renal dynamic angioscintigraphy with DTPA-Tc99m, and ophtalmoscopy were performed. Results. Renal dynamic angioscintigraphy with DTPA-Tc99m revealed various renal hemodynamics abnormalities in 98% of the patients (n=41). In most individuals (94%; n=39), renal blood flow was reduced. Ophtalmoscopy revealed initial stages of hypertensive retinopathy in 22 patients (52%). Participants with hypertensive retinopathy experienced decrease in renal blood flow of Stage II-III more often, by 17%: the decline was registered in 77% and 50% of the patients with or without hypertensive retinopathy, respectively. Therefore, retinopathy was associated with more severe abnormalities of renal hemodynamics. Conclusion. In early AH stages, young patients, aged under 35, experience vascular remodeling even with high BP anamnesis as short as 1-7 years. There is a need for early administration of antihypertensive therapy, especially ACE inhibitors.